Fundamentals of Music Processing - Müller, Meinard (Springer, 2021)
Combines foundational technologies and essential applications in music processing and music information retrieval Chapters can be read independently and thus serve as building blocks for individually structured courses Each chapter is complemented with many examples, figures, exercises, and references for further reading Related Web page includes additional audio-visual material and Python code exampl
Keywords: Audio Retrieval; Fourier Analysis; Music Computing; Music Retrieval; Music Structure Analysis; Pattern Recognition; Signal Processing; Sound Computing; Pattern Recognition; Signal; Image and Speech Processing; Information Storage and Retrieval; Fourier Analysis; Computer Appl. in Arts and Humanities; Music